Pengembangan Sistem Manajemen Farmasi Di Pelayanan Kesehatan Rumah Sakit: Studi Teoritis - Jimmy Triputra; Dety Mulyanti (Jurnal Kesehatan Amanah, 2023)
The hospital as a health service facility that carries out health efforts in an efficient and effective manner in healing and recovery efforts that are integrated with efforts to improve and prevent disease. In developing the hospital, it is also necessary to develop a management system service. One approach that can be taken to measure the success of an information system is to assess and develop pharmaceutical management. according to professional responsibilities. The purpose of this theoretical review is to find out how to develop a pharmaceutical management system in hospital health services. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review are data processing, innovation, information and response from a management system. A pharmaceutical information system is an organized system for collecting, processing, reporting, and using information for decision making. Information is obtained from integrated collection of pharmaceutical documents or records and continuous development. It is also necessary to develop innovation and update a more modern pharmaceutical management system to simplify and streamline the healthcare system.